FAKTOR YANG BERHUBUNGAN DENGAN STRES KERJA PERAWAT DI RUANG IGD RUMAH SAKIT : SISTEMATIK REVIEW - Suhadi, Suhadi; Sukurni, Sukurni (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2021)
Nursing is naturally a stressful job. Stress on nurses can lead to depression, isolation from patients, absenteeism and a decrease in their qualifications. The purpose of this study was to review factors related to work stress on nurses who work in hospitals. This type of research includes observational analytic using a cross sectional study with a sample size of 26 to 106 respondents. The dominant research results in the collected articles concluded that factors related to nurse work stress such as working conditions, coping mechanisms, work violence, physical workload, and mental workload. The results of this article review can be used as reference material for the hospital in improving services by preventing work stress on nurses